Pemetaan Publikasi Mengenai Corporate Performance di Negara-negara Asean - Fauzan Fauzan; Adi Susilo Jahja (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
This study aims to investigate the trend of documents related to “corporate performance” based on data obtained from the Scopus bibliographic database. The intellectual structure of research on corporate performance and its development was identified from 1987 to 2021. Data taken from the Scopus database on Thursday, November 26, 2020, at 7.34 WIB, obtained 27,913 documents related to corporate performance. However, after sorting by type of document (article), type of source (journal), country (ASEAN countries), 2,280 documents were obtained for analysis. The applications used are VOSviewer and Harzing's Publish or Perish. This article reports on document types and sources, research productivity, language used in publications, subject areas, titles of most active sources, distribution of publications by country, most active institutions, authorship, keywords, abstract titles and analysis, and citation analysis. The results show that there is an increase in the rate of growth of the literature on corporate performance from 1987 to 2021. A sharp increase occurred in 2013 to 2020. Research on corporate performance involving the collaboration of various authors has been published in various languages, written by 317 authors from 286 institutions in 10 ASEAN countries.Keywords: Bibliometric analysis, VOSviewer, corporate performance, ASEAN.